2014
DOI: 10.1209/0295-5075/105/60002
|View full text |Cite
|
Sign up to set email alerts
|

Can scale-freeness offset delayed signal detection in neuronal networks?

Abstract: -First spike latency following stimulus onset is of significant physiological relevance. Neurons transmit information about their inputs by transforming them into spike trains, and the timing of these spike trains is in turn crucial for effectively encoding that information. Random processes and uncertainty that underly neuronal dynamics have been shown to prolong the time towards the first response in a phenomenon dubbed noise-delayed decay. Here we study whether Hodgkin-Huxley neurons with a tunable intensit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 47 publications
(68 reference statements)
0
12
0
Order By: Relevance
“…Since Hodgkin and Huxley's pioneering work [31], the role of noise has been extensively studied in the generation and propagation of the membrane potential of neurons, and stochastic resonance (SR) and coherence resonance (CR) have been found in various neuronal systems (see e.g., [32][33][34]). In recent decade, some SR and CR phenomena due to channel noise in neuronal networks have been found, such as sodium and potassium channel block reduced and enhanced spiking coherence of neuronal network, respectively [35,36], channel noise enhanced propagation of pacemaker signals across neuronal networks [37] and weak signal across feed-forward neuronal networks [38], and channel noise decreased mean latency and jitter of the first spikes in response to subthreshold signal [39,40] and degraded signal detection capability of neuronal network [41], as well as channel block resonantly enhanced spiking regularity of clustered neuronal networks [42]. It is also shown that noise can induce and enhance synchronization in excitable media [43], coupled thermo-sensitive neurons [44], and neuronal networks [45].…”
Section: Introductionmentioning
confidence: 99%
“…Since Hodgkin and Huxley's pioneering work [31], the role of noise has been extensively studied in the generation and propagation of the membrane potential of neurons, and stochastic resonance (SR) and coherence resonance (CR) have been found in various neuronal systems (see e.g., [32][33][34]). In recent decade, some SR and CR phenomena due to channel noise in neuronal networks have been found, such as sodium and potassium channel block reduced and enhanced spiking coherence of neuronal network, respectively [35,36], channel noise enhanced propagation of pacemaker signals across neuronal networks [37] and weak signal across feed-forward neuronal networks [38], and channel noise decreased mean latency and jitter of the first spikes in response to subthreshold signal [39,40] and degraded signal detection capability of neuronal network [41], as well as channel block resonantly enhanced spiking regularity of clustered neuronal networks [42]. It is also shown that noise can induce and enhance synchronization in excitable media [43], coupled thermo-sensitive neurons [44], and neuronal networks [45].…”
Section: Introductionmentioning
confidence: 99%
“…In equation (1), GNa, GK and GL denote sodium, potassium and leakage ion channel conductance, respectively. In the model, the leakage conductance is constant, GL=0.3mScm -2 , whereas the others dynamically change as follows [30,34,37,38]:…”
Section: Model and Methodsmentioning
confidence: 99%
“…For a given membrane, by a fine-tuned addition of these toxins a certain portion of potassium-and sodium ion channels could be disabled or blocked and hence the number of active (working) ion channels can be reduced. There are also plenty of studies based on different computational neuron models, where the impacts of changing the number of particular ion channels on firing dynamics of a single neuron or neuronal networks' is examined [30][31][32][33][34][35][36][37][38]. In these studies, it is uncovered that channel blocking has crucial impacts on firing dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the wellknown neuron models, networks with different topological connections have been set to investigate the synchronization stability [36,37], pattern selection, and mode transition in collective behaviors [38][39][40][41][42][43][44][45]. Indeed, reliable and biophysical neuron model is critical and important for further investigation on neurodynamics and potential mechanism of some neuronal diseases [46].…”
Section: Complexitymentioning
confidence: 99%